THE COUNSELING TECHNIQUE TO REDUCE SPEAKING ANXIETY IN THE PERSPECTIVE OF PRAGMATIC THEORY - Fharoza Yuliska Putri; Muhammad Nurwahidin; Sudjarwo Sudjarwo (Jurnal Ilmiah Hospitality, 2022)
Speaking ability is an important aspect of human life that is interesting and complex and is much needed by students in learning process. But unfortunately not everyone has good and trained public speaking skills. The existence of speaking anxiety felt by students is often an obstacle in carrying out assignments and building social relationships. Speaking anxiety is a form of feeling anxious or afraid with several psychological symptoms. Considering that the symptoms caused by speaking anxiety can have an impact on disrupting student activities in the interaction process and the learning process, it is felt that an action is needed to provide a solution. Several counseling approach techniques have been tested in various studies as will be explained in this study, formulation of the problem including what are the effects/symptoms of speaking anxiety and then it will also be studied for its axiological basis in the perspective of a pragmatic theory of truth which will look at the usefulness of the results of various the research. The researcher aimed to find out the impact/symptoms of speaking anxiety and to see the value of the intervention of various guidance and counseling techniques to reduce speaking anxiety. In this research, the researcher used the literature study method. The results and findings from this literature study are that there are several psychological symptoms such as body shaking, sweating, fast heart beats and so on and the effectiveness of various counseling interventions have proven to reducing the level of students’ speaking anxiety. Students who were given guidance counseling interventions experienced a decrease in their speaking anxiety level scores.